2011
DOI: 10.1007/s00423-011-0862-z
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative short-term parenteral administration of polyunsaturated fatty acids ameliorates intestinal inflammation and postoperative ileus in rodents

Abstract: Short-term preoperative parenteral administration of (n-3) or (n-6) PUFA-LE significantly alters tissue-specific fatty acid profiles. Preoperative parenteral PUFA-LE supplementation, preferably by marine (n-3) PUFA, ameliorates postoperative intestinal inflammation and dysmotility and could be a promising therapeutic option in POI prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 46 publications
(66 reference statements)
1
13
0
1
Order By: Relevance
“…In addition, the intestinal tissue pathological scores in the FO + NEC group were much lower than those in the NEC group. Consistent with these findings, ω-3 PUFAs were earlier shown to ameliorate postoperative intestinal inflammation and dysmotility 24 . DHA administration was shown to attenuate activation of inflammasomes induced by macrophage-derived TNF-α 25 .…”
Section: Discussionsupporting
confidence: 69%
“…In addition, the intestinal tissue pathological scores in the FO + NEC group were much lower than those in the NEC group. Consistent with these findings, ω-3 PUFAs were earlier shown to ameliorate postoperative intestinal inflammation and dysmotility 24 . DHA administration was shown to attenuate activation of inflammasomes induced by macrophage-derived TNF-α 25 .…”
Section: Discussionsupporting
confidence: 69%
“…Indeed, cellular eicosanoids profiles differed between patients that were perioperatively treated with different PUFA [74,75]. In a recent study, our group demonstrated that preoperative intravenous ω-3 PUFA application significantly ameliorated neutrophil influx and intestinal dysmotility after intestinal manipulation [76]. Gas chromatografical analyses confirmed that intestinal tissues as well as bone marrow cells demonstrated significant changes with an increase of supplemented PUFA reflecting the administered lipid emulsions.…”
Section: Immunomodulatory Nutrientsmentioning
confidence: 75%
“…Recent meta-analyses show that enteral immunonutrition regimes, which include omega-3 supplements, may optimize recovery of patients who undergo elective surgery for GI cancer, especially when delivered in the perioperative period 12,13 , while some parenteral models of omega-3 supplementation have also shown beneficial effects 14,15 . In murine models a similar mixed picture exists, but in congruence with human models a majority of studies providing FO supplementation over periods of 5 days to 12 weeks display downstream resolution-favoring changes in mRNA expression of classical M1/M2 macrophage markers of maturation 16 , inflammatory cytokine and lipid profile [17][18][19] , efferocytosis 20 , and immune cell oxidative potency 6 , with additional reports indicating that oral FO takes 24-72 hours to induce beneficial metabolic effects 7 .…”
Section: Introductionmentioning
confidence: 82%